SPOT - jogo sério baseado em realidade aumentada para a prevenção do melanoma - Ana Catarina Rodrigues Ferreira (2021)
In this project, melanoma is addressed as the deadliest cancer of all skin cancers, contrasting with these numbers, there is a high rate of emergency when it is detected early, and exists prevention. In order to modify these numbers it is necessary to have a secondary prevention, the self-examination of the skin where the ABCDE method is used. The population, in general, doesn't know the importance of self-examination and it is important to teachin the best way, through a serious game using augmented reality technology. To reach the point of awareness we have to use technology as an ally in the need to educate people and for that we will use augmented reality as a way to show reality that doesn't exist in us. The gamification part will accompany augmented reality technology so that the player feels the captivation, fun and all the immersion to have a behavioral change. The main objective is to create a serious game using augmented reality technology to encourage the learning of skin self-examination with the ABCDE method. An initial prototype was developed in order to get a feel for the usability of the initial game, doing some tests. The results proved the effectiveness of augmented reality in raising awareness of skin self-examination, and also demonstrates that the proposed concept motivates self-examination learning. The SPOT application is a serious game that pretend to promote the learning of the ABCDE method, using augmented reality and gamification. The user has a tutorial section where they will learn the meaning of the various letters of the method and, at the end, will have a game to put their knowledge into practice, always having a score that is able to see their level of understanding regarding the ABCDE method.